Analysis of the Influence of Marketing Strategy 4.0 on Consumer Satisfaction and Repurchase Intention of RTD Products in the Carbonated Soft Drink Category - Dewi, Aprilyta Gadis Nabilla (Syntax Literate, 2025)
This study aims to analyze the impact of the Marketing 4.0 strategy on consumer satisfaction and repurchase intention for Ready-to-Drink (RTD) carbonated soft drinks (CSD). Marketing 4.0, introduced by Kotler, Kartajaya, and Setiawan, integrates digital and traditional marketing through four key elements: Brand Identity, Brand Image, Brand Integrity, and Brand Interaction. The research uses Partial Least Squares - Structural Equation Modeling (PLS-SEM) with 524 respondents, who are CSD consumers in Indonesia. The results show that Brand Identity, Brand Image, and Brand Integrity have a positive and significant impact on consumer satisfaction, while Brand Interaction has a positive but non-significant impact. For repurchase intention, Brand Image, Brand Integrity, and Brand Interaction have a positive and significant effect, while Brand Identity has a negative but non-significant impact. Cross-tabulation analysis reveals a significant relationship between consumer satisfaction, repurchase intention, and demographic factors such as age, purchase location, and purchase frequency. This study offers practical insights for marketers to develop more effective strategies to enhance consumer loyalty and provides academic contributions regarding the relevance of Marketing 4.0 for low involvement products.